Creativity in the classroom schools of curious delight - Starko, Alane J. (New York Routledge, 2018)
"Creativity in the Classroom, sixth edition, helps teachers link creativity research and theory to the everyday activities of classroom teaching. This foundational textbook is relevant for any course dealing wholly or partially with creativity and teaching. The sixth edition has been revised and updated throughout, informed by cutting-edge research on neurobiology, curiosity and imaginative play, questioning, and motivation, particularly the relationships among creativity, intrinsic motivation, and motivation to learn"--Provided by publisher.
Part I: Understanding Creative People and Processes -- 1. What is Creativity? -- 2. Models of the Creative Process -- 3. Theories of Creativity: The Individual -- 4. Theories of Creativity: Systems in Context -- 5. Creative People -- Part II: Creativity and Classroom Life -- 6. Teaching Creative Thinking Skills and Habits -- 7. Creativity in the Content Areas: Language Arts, Social Studies, and the Arts -- 8. Creativity in the Content Areas: Science, Math, and General Teaching Strategies -- 9. Motivation, Creativity, and Classroom Organization -- 10. Assessment and Creativity
Keywords: Creative thinking